STUDY ON HIGH TEMPERATURE CREEP PROPERTIES OF DOMESTIC 800HT ALLOY USING SMALL PUNCH TEST TECHNIQUE - JIANG Tao; GUAN KaiShu; ZHONG JiRu (Jixie qiangdu)
The creep performance of a domestic high⁃temperature incoloy 800HT alloy was tested using the small punch creep test technique.The CWA small punch creep test conversion method,and the EFS and MCH conversion methods were used respectively.The results of the uniaxial creep tests were compared with the small punch creep test results.The results show that,for small punch creep test data of 800HT alloy,the CWA method outperforms the EFS and MCH conversion methods.When fitting the uniaxial creep data,the Wilshire founction,which takes into account the creep activation energy in the yield state,correlates well with the 800HT creep data.With the small punch creep test technique,the requirements for determining the high temperature creep properties of the domestic 800HT alloy can be met.